Investigating how survivin expression affects the cell death response induced by UV irradiation - Coe, Kirstie Danielle (2020)
Survivin is a multi-functional protein with documented roles in both cell death and proliferation. Over-expression of survivin has been observed in several cancer types and due to its pro-survival activities, it is an ideal target for onotherapy. However, there are still many unanswered questions surrounding the role of survivin in cancer. Furthermore, a cancer specific mitochondrial pool of survivin exists that is thought to be important for its role in inhibiting apoptosis, as the mitochondria are common sites for apoptosis initiation. To support this, previous research has shown that removal of its bona fide mitochondrial targeting sequence represses the anti-apoptotic function of survivin. Therefore, the aim of this thesis was to investigate the role of mitochondrial survivin in protecting cancerous cells from UV-induced apoptosis.